2022
DOI: 10.2166/wst.2022.085
|View full text |Cite
|
Sign up to set email alerts
|

Adsorption of Congo red and tetracycline onto water treatment sludge biochar: characterisation, kinetic, equilibrium and thermodynamic study

Abstract: In this study, readily available inexpensive water treatment sludge (WTS) was used to prepare adsorbent for the removal of Congo red (CR) and tetracycline (TC) from aqueous solutions. The structural characteristics and adsorption properties of WTS biochar were characterised via scanning electron microscope, energy dispersive X − ray spectroscopy, Brunauer − Emmett − Teller and Fourier Transform infrared spectroscopy. In batch experiments, the adsorption factors, kinetics, isothermal curves and thermodynamics o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
11
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 20 publications
(13 citation statements)
references
References 58 publications
2
11
0
Order By: Relevance
“…A number of studies found that the optimal temperature range for thermal activation is up to 600 °C, after which crystalline transformation of amorphous Al/Fe WTRs into mineral crystals starts taking place [ 20 ]. Some of the researchers attempted to reuse WTRs by modifying it to a more reliable porous material, such as biochar via pyrolysis, an oxygen-limited thermal treatment, and hydrochar via hydrothermal carbonization [ 50 , 51 ]. This enhances its adsorption potential for various organic and inorganic pollutants by increasing adsorption sites related to Al and Fe [ 52 ].…”
Section: Modification Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…A number of studies found that the optimal temperature range for thermal activation is up to 600 °C, after which crystalline transformation of amorphous Al/Fe WTRs into mineral crystals starts taking place [ 20 ]. Some of the researchers attempted to reuse WTRs by modifying it to a more reliable porous material, such as biochar via pyrolysis, an oxygen-limited thermal treatment, and hydrochar via hydrothermal carbonization [ 50 , 51 ]. This enhances its adsorption potential for various organic and inorganic pollutants by increasing adsorption sites related to Al and Fe [ 52 ].…”
Section: Modification Methodsmentioning
confidence: 99%
“…It is the pH at which net surface charge on the surface become neutral and the numbers of positive and negative charges of the adsorbent are equal [ 6 ]. The pH pzc value aids in interpretation of the adsorption potential of modified WTRs under different pH values [ 1 , 51 ]. When the solution pH exceeds pH pzc , the surface of adsorbents is negatively charged showing strong potential to attract positively charged pollutants such as methylene blue, Pb 2+ and Cu +2 .…”
Section: Characteristics Of Water Treatment Residualsmentioning
confidence: 99%
See 1 more Smart Citation
“…To study the adsorption of TC onto biochar, the following kinetic models were used in their linear forms [23,28]:…”
Section: Equilibrium Studies and Kinetic Modelsmentioning
confidence: 99%
“…The biochar produced at 700 • C achieved a maximum removal efficiency of approximately 47% at pH = 3 and a biochar dose of 1.25 g/L [22]. With biochar prepared from a water treatment plant's sludge and used for TC adsorption, the removal efficiency achieved was 96.72% at a biochar dose of 4 g/L and an initial TC concentration of 60 mg/L [23]. ZVI@biochar has been used to remove tetracycline, oxytetracycline (OTC), and chlortetracycline (CTC) from aqueous solutions and wastewater.…”
Section: Introductionmentioning
confidence: 99%